2021
DOI: 10.1242/dev.195495
|View full text |Cite
|
Sign up to set email alerts
|

SMAD2 promotes myogenin expression and terminal myogenic differentiation

Abstract: SMAD2 is a transcription factor whose activity is regulated by members of the Transforming Growth Factor beta (TGFβ) superfamily. While activation of SMAD2 and SMAD3 downstream of TGFβ or myostatin signaling is known to inhibit myogenesis, we find that SMAD2 in the absence of TGFβ signaling promotes terminal myogenic differentiation. We find that during myogenic differentiation, SMAD2 expression is induced. Knockout of SMAD2 expression in primary myoblasts did not affect the efficiency of myogenic differentiat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Recently, a study on the downstream target gene Smad2 of MSTN showed that the knock-out of Smad2 expression in primary myoblasts did not affect the efficiency of myogenic differentiation, but produced smaller myotubes with reduced expression of the terminal differentiation marker myogenin. In turn, the overexpression of Smad2 stimulated the expression of myogenin and enhanced cell differentiation and fusion (Lamarche et al , 2021). In our study, the MSTN Del273C mutation with FGF5 knockout resulted in the inhibition of myogenic differentiation of skeletal muscle satellite cells, and the number of myotubes and the myotube size were significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study on the downstream target gene Smad2 of MSTN showed that the knock-out of Smad2 expression in primary myoblasts did not affect the efficiency of myogenic differentiation, but produced smaller myotubes with reduced expression of the terminal differentiation marker myogenin. In turn, the overexpression of Smad2 stimulated the expression of myogenin and enhanced cell differentiation and fusion (Lamarche et al , 2021). In our study, the MSTN Del273C mutation with FGF5 knockout resulted in the inhibition of myogenic differentiation of skeletal muscle satellite cells, and the number of myotubes and the myotube size were significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, myostatin decreases the diameter of differentiated myotubes (Trendelenburg et al, 2009). Recently, a study on the downstream target of myostatin, Smad2, showed that the knock-out of Smad2 expression in primary myoblasts does not affect the efficiency of myogenic differentiation but produces smaller myotubes with reduced expression of the terminal differentiation marker, myogenin; conversely, overexpression of Smad2 stimulates the expression of myogenin and enhances cell differentiation and fusion (Lamarche et al, 2021).…”
Section: Myostatin Regulates Skeletal Muscle Growth and Development Myostatin Regulates The Proliferation And Differentiation Of Skeletalmentioning
confidence: 99%
“…After being stimulated by external harmful factors, the expression of myogenic regulatory factors (MRFs) such as Myf5, MRF4, myogenic differentiation antigen (MyoD), and myogenin (MyoG) is up‐regulated in satellite cells to activate myogenic differentiation and myotube formation for damaged muscles repair and regeneration 24,25 . Furthermore, MyoG protein level is also considered as an early marker of the myogenic differentiation process 26 . Beta‐myosin heavy chain (MyHC), an important functional motor protein, is the basic unit of thick filament of skeletal muscle fibers and generally regarded as a marker protein of the stage of myoblast differentiation 27,28 .…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Furthermore, MyoG protein level is also considered as an early marker of the myogenic differentiation process. 26 Betamyosin heavy chain (MyHC), an important functional motor protein, is the basic unit of thick filament of skeletal muscle fibers and generally regarded as a marker protein of the stage of myoblast differentiation. 27,28 Myostatin (MSTN) is a class of growth regulator with the function of inhibiting muscle growth.…”
Section: Introductionmentioning
confidence: 99%